HARMONIZING FAITH AND VIRTUE: ENHACING DISCIPLINE THROUGH ISLAMIC EDUCATION AND CHARACTER BUILDING IN PALOPO CITY SCHOOLS - Ilham, Dodi; Pirol, Abdul; Baderiah; A. Zainuddin, Andi Husni; Hamrul, Aisyah Yuspita (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research investigates discipline values in primary education by integrating Islamic religious education and character education in Palopo City. Using a mixed methods approach with a socio-cultural education perspective, the study covers nine Palopo and South Sulawesi districts. The sampling included 27 teachers from Islamic religious education and character education and 100 students from a total population of 17,647. Data collection methods comprised observation, questionnaires, interviews, and documentation. The study found that the content of the books aligns with disciplinary indicators, emphasizing the crucial role of teachers in integrating these values into the curriculum. Eight key sub-indicators, such as Commitment, Punctuality, and Obedience, were identified as focal points for reinforcing discipline. The dominant approach includes role modelling, honesty, canteen programs, and instilling beliefs. The findings highlight the significance of teachers in conveying disciplinary values, emphasizing the need for further efforts to link these values with specific sub-indicators. Continuous evaluation and innovation are crucial for optimal understanding of disciplinary values. The research enhances the effectiveness of Islamic religious education and character education in promoting discipline values in primary education in Palopo City.